Implementasi Sistem OSS dalam Pelayanan Perizinan Berusaha di Mal Pelayanan Publik Kabupaten Sidoarjo - Artika Nur Sofarika; Tukiman Tukiman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
The implementation of the Online Single Submission (OSS) system is part of the government's policy to facilitate business and simplify licensing bureaucracy. In the context of regional public services, the Sidoarjo Regency Public Service Mall (MPP) acts as an integrated service center that supports the implementation of OSS in business licensing services. This study aims to analyze the implementation of the OSS system in business licensing services at the MPP of Sidoarjo Regency by applying the perspective of policy implementation theory, which includes aspects of disposition, communication, bureaucratic structure, and resources. This study uses a qualitative approach with a descriptive-analytical research type. Data were collected through observation and interviews, then analyzed comprehensively to describe the conditions of OSS implementation in the field. Informants were selected using purposive and snowball sampling, considering the relevance of the informants to the research focus. The results of the study show that the implementation of OSS in the Sidoarjo Regency MPP has basically been running and has made a positive contribution in supporting business licensing services. The aspects of disposition and bureaucratic structure show relatively good conditions, marked by the responsive attitude of officers, the existence of clear SOPs, and functional coordination between agencies. However, limitations were still found in the aspects of communication and resources, particularly in relation to the dissemination of information on the OSS system update and the technical readiness of the apparatus. Therefore, it is necessary to strengthen dissemination, increase human resource capacity, and optimize supporting facilities so that the objectives of the business facilitation policy can be achieved more optimally.